The uncertain burden of Plasmodium falciparum epidemics in Africa - Cox, J; Hay, S; Abeku, T; Checchi, F; Snow, R (Elsevier, 2007)
Although the control of malaria epidemics has been a priority for the World Health Organization and other agencies for many years, surprisingly little is known about the public health burden of these epidemics. Here, we evaluate the available evidence of the morbidity and mortality impacts of individual epidemics in Africa and examine the problems associated with using these data to estimate the average annual burden of epidemics at national and continental scales. We argue that conventional approaches that are used to assess the burden of epidemics are inadequate, and outline the future steps that are required to produce estimates that are more accurate.